Development of heterogeneous base catayst for transesterification reaction - Sharmilla, Arumugam (2010)
In this study of heterogeneous base catalyst of potassium nitrate with alumina support was investigated for transesterification of vegetable oil which is palm oil to methyl ester. The environmental problem could be overcome by using heterogeneous base catalyst because the separation of catalyst from final product is easier without use of any solvent and the catalyst is recyclable. The objective of this study is to characterise the developed heterogeneous base catalyst and test it in transesterification reaction at different operating parameters such as molar ratio of methanol to oil, reaction temperature and catalyst loading. After loading potassium nitrate of 35 wt.% on alumina followed by calcination at 773K for 5 h, the catalyst gave the highest basicity and the best catalytic activity for this reaction. The catalysts were characterized by using Fourier Transform Infrared Spectrometers (FTIR) and Scanning Electron Microscopy (SEM). It was found that KNO3/ Al2O show high activity which converting 78.44% of palm oil to methyl ester with the optimum conditions which are at temperature 65°C, methanol to oil ratio of 15:1 and catalyst loading of 8.5% . Therefore, base heterogeneous catalyst of potassium on alumina of support has the potential to be used in biodiesel production processes due to its high activity on transesterification of palm oil.